The impact of cognitive schema on learning transfer ability and stability of classical Chinese poetry - Dawei Liu; Ping He; Huifen Yan (PLoS ONE, 2025)
Classical Chinese poetry is a condensed vessel of Chinese culture, bearing the core ethos of history, philosophy, and ethics. The symbolic imagery system in poetry facilitates the construction of cognitive schemata, thereby advancing transfer learning. Based on Schema Theory and Cognitive Structure Migration Theory, this research conducted a controlled experiment, with the participants being undergraduate students, to examine how “cognitive schema’‘ influences transfer ability and stability in learning classical Chinese poetry. The results revealed that the experimental group (n = 63) achieved higher scores in both tests, indicating that learners who employed the cognitive schema learning method demonstrated greater transfer ability and stability than the control group (n = 64). Significant differences in results between the experimental group and control group highlighted the positive impact of cognitive schema on learners’ transfer ability and stability in learning classical Chinese poetry. It is hoped that this research will provide valuable implications for the teaching and learning of classical Chinese poetry.